WebSphere Studio Application Monitor V3.2 advanced usage guide - Darmawan, Budi (IBM redbooks., 2005)
The addition of WebSphere Studio Application Monitor to the Tivoli product portfolio enhanced Tivoli offerings for application management. WebSphere Studio Application Monitor enables comprehensive monitoring and management of J2EE-based applications with their back-end platforms. This IBM Redbooks publication demonstrates advanced uses of WebSphere Studio Application Monitor to solve day-to-day operational problems. The book is intended for system administrators who want to use WebSphere Studio Application Monitor for monitoring Web-based applications. We do not discuss implementation issues in this book. We present WebSphere Studio Application Monitor concepts and offer usage details such as: - System administration of day-to-day operations, from grouping and security design to maintenance tasks. - Problem determination for WebSphere-based applications to assist with common problems that may occur in your environment. - Management and analysis of composite applications, which span multiple application servers and can be hard to manage, with demonstrations of composite applications across J2EE servers, CICS, and IMS. Please note that the additional material referenced in the text is not available from IBM.